Polycondensation of a perylene bisimide derivative and L-malic acid as water-soluble conjugates for fluorescent labeling of live mammalian cells - He, Ji (2018)
Based on simple mixing and polymerization of a hydroxyl-containing derivative of perylene bisimide (PBI) and l-malic acid, here, we demonstrate a new type of dye-polymer conjugate, PBI-poly(α,β-malic acid) (PBI–PMA). Benefiting from the excellent water-solubility of weak polyanionic PMA structure and the high fluorescence of PBI, the PBI-PMA conjugates readily dissolve in water, displaying strong pH-dependent fluorescence with the highest intensity at pH 6. Due to the excellent biocompatibility of PMA, those conjugates showed low cytotoxicity on L929 cells. Using L929 and HeLa cells, we also confirmed that the PBI-PMA-labeled cells display intense fluorescence. Overall, the PBI-PMA conjugate demonstrates high potential as a cell labeling agent with its synthesis ease, good solubility in aqueous medium, low cytotoxicity, and high fluorescence.